Comparative Biological Studies Of Allicin With Paeonol. - F.REHMAN; SAMYA MAIRAJ (International Journal of Pharma and Bio Sciences, 2012)
It has been reported that Allium Sativum contains a large number of essential metal, carbohydrate, protein,vitamins and volatile oil and allicin is one of the active ingredient of freshly crushed garlic homogenates and has a variety of antimicrobial activities and used to prevent the heart diseases that include artherosclerosis, high cholesterol and high blood pressure. Antimicrobial activity of allicin is mainly due to S-S and S-O bond which has the ability to react with thiol containing enzyme to form S-thiolation product, the broad spectrum antimicrobial effects of allicin is due to the multiple inhibitory effects on various thiol dependent enzymatic systems. Anticholesterol activity was tested by standard method and results shows that cholesterol level (LDL) decrease significantly, when allicin is used for 8-12 week. The antimicrobial activity of different concentration of ligand and paeonol were measured by determining the growth of test fungus and bacteria by dry weight increased method and by agar diffusion method against Aspergillus flavus, Aspergillus niger,Cryptococcus neformons & Allternaria alternate fungi Streproproteus, staphylococcus & E.Coli bacteria. The results indicate that allicin has more antimicrobial properties as compare to paeonol. The activity index for different microbes have also been calculated.